Numerical simulation and experiment of the gas-liquid two-phase flow in the pigging process based on bypass state. (15th May 2022) - Chen, Shengtao; Zhang, Yibo; Wang, Xiaolu; Teng, Kai; Gong, Yongjun; Qu, Yichen
Abstract: In the pigging of long-distance gas-liquid pipelines, the sealing disks and the inner wall of the pipeline will inevitably wear out. This may cause the diameter of the pig seal disks to be smaller than the inner diameter of the pipe, resulting in a clearance. The presence of clearance has a significant influence on the liquid flow pattern. Aiming to explore liquid flow characteristics in the pipeline, the paper conducted a series of numeric simulations based on the CFD method to investigate the process. The calculated model and experimental data verified the accuracy of simulations. Our results show that both the front and back of the pig are gas-liquid two-phase flow, and the higher the clearance, the lower the volume fraction of the liquid slug at the front of the pig. The increase in the speed of the pig will increase the length of the liquid slug segment and the front-end speed of the liquid slug. And as the inlet gas velocity gradually increases, the liquid at the front of the pig gradually scatters and becomes chaotic. The time for the liquid to reach the terminal outlet is only related to the pig speed. When increasing the clearance, the residual liquid in the pipeline increases, and the pigging effect worsens. Our results can provide some reference in pigging of gas-liquid pipelines. Highlights: A overset moving grid pigging simulation is proposed. Gas-liquid two-phase flow of pigging is elucidated. Inlet gas velocity has a great influence on the liquid phase distribution.